(untitled) (Impact: Journal of Transformation, 2019)
Masturbation, a form of sexual expression, has been associated with other sexual behaviors. This makes it an important component of youth sexuality rather than an isolated phenomenon. To understand fully sexual expressions among youths, the issue of masturbation must be given a critical focus especially as there seems to be no general consensus as to its appropriateness as a way of expressing sexual urge. The purpose of this study, therefore, is to identify the problem with masturbation, its causes, and its ethical implications from a religious perspective and thereafter prescribe the right response. This work employed the survey method of gathering information. Seven hundred copies of questionnaires were administered to 120 churches in 10 Baptist associations in Ibadan Conference, Nigeria. Findings reveal that masturbation is a common experience among youths. Most (84.5%) of the respondents have heard about masturbation and 80.1% defined it as intentionally playing with one’s sexual organ until orgasm is reached. Of the respondents, 61.7% have masturbated at least once. Many (71.1%) of the respondents strongly agreed that it is not the best way to express sexual urge. A majority (69.4%) see it as a sin a youth should avoid. This is possible by avoiding printed materials, movies, or situations that may easily stir sexual urge. The study concludes that masturbation is a subject of great confusion among religious adherents, especially youths. The study, therefore, recommends that both parents and the church be responsive in identifying with young people in their struggles with sexual problems and provide a healthy environment for them where they can develop a balanced perception about their sexuality. It also recommends that since we live in a sexually-saturated environment, every young person should be disciplined with regard to what they see and hear so as to sustain their moral values.